Precut bonanza! : 200 pieced blocks from cut strips and shapes - Einmo, Kimberly (American Quilter's Society, 2012)
"Reference guide to piecing precut fabric, whether purchased or cut from your stash! Follow Kimberly's easy method of using simple, basic units such as squares, half-square triangles, four-patch units, and more to create more complex units and blocks. Pattern instructions for 3 sampler quilts, a gallery for inspiration, and Kimberly's familiar tips"--Provided by publisher.